Factors driving e-learning adoption in Palestine: An integration of technology acceptance model and is success mode - Ziad Aldammagh; Rabah Abdaljawad; Tareq Obaid (Financial Internet Quarterly, 2021)
One of the most significant changes in the field of education in this information age is the paradigm shift from teacher-centered to learner-centered education. Along with this paradigm shift, understanding of students' e-learning adoption behavior among various countries is urgently needed. Despite being one of the many countries that are still at the early stages in implementing e-learning, Palestine is a country that has recently seen an expansion in the number of students and the quality of education, which has involved high investment in e-learning. Hence, studies in this area of research interest have yet to be made known within the field of education. This study attempted to address the disparity within the literature for an individual country, Palestine, on the significant influences towards adopting e-learning. A model that investigates the effects of quality features, perceived ease of use, perceived usefulness on the intentions and satisfaction of the learners towards the effects of e-learning is proposed in this study. This model encompassed the constructs and variables embedded in TAM and ISSM along with instructor quality. The outcomes of the model, such as actual use and the moderating effect of technical support towards e-learning in Palestine, were investigated. The study proposed that the quality of the course, instructor, service and system as well as perceived usefulness determined the satisfaction among students in use e-learning.
Keywords: I23; 330; e-Learning; satisfaction; quality; intention; the actual use